2017
DOI: 10.1186/s13256-017-1440-y
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid volvulus in children: a case report

Abstract: BackgroundSigmoid volvulus is frequently reported in the “volvulus belt” (Middle East, Africa, the Indian subcontinent, Turkey, and South America) and is the third leading cause of large bowel obstruction in North America.It is an uncommon problem in children and adolescents, and is rarely considered a diagnosis in this group. A high index of suspicion is necessary to diagnose sigmoid volvulus in children.Case presentationWe present a 13-year-old Arabian girl who came with features suggestive of intestinal obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…1 If a non-operative approach is unsuccessful at reducing the volvulus or the patient develops signs of perforation/peritonitis, then immediate surgery is warranted. 2 We decided to operate because of the greatly dilated colon and fear of perforation in our case. According to Salas et al., 14 sigmoidectomy with either primary anastomosis or colostomy is the definitive treatment for SV.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1 If a non-operative approach is unsuccessful at reducing the volvulus or the patient develops signs of perforation/peritonitis, then immediate surgery is warranted. 2 We decided to operate because of the greatly dilated colon and fear of perforation in our case. According to Salas et al., 14 sigmoidectomy with either primary anastomosis or colostomy is the definitive treatment for SV.…”
Section: Discussionmentioning
confidence: 93%
“…However, a characteristic geographical distribution of SV is absent in the pediatric population, and thus the cause of SV is unclear. 1,2 The exact incidence of SV in children is still unknown. There have only been a few case reports and a relatively small case series on SV, with only 93 cases of SV reported worldwide by 2007, 1,3 and only a few more reported by 2020.…”
Section: Introductionmentioning
confidence: 99%
“…It is more common in males and occurs in ratios ranging from 2:1 to 10:1. Although volvulus in adults is common in Asian populations, in pediatric surgical practice volvulus of the sigmoid colon remains a rare occurrence and only a few isolated case reports and case series have been reported [ 1 , 10 ]. Salas et al [ 3 ] has stated the median age at presentation 7 years, ranging from 4 h to 18 years in pediatric sigmoid volvulus and boys-to-girls ratio being 3.5 to 1 however, Slidell et al reported three teenagers ages 17–19 with sigmoid volvulus [ 11 ] and T.R.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal pain, distention, and constipation are the classical triad of symptoms in acute sigmoid volvulus. Additional complaints include vomiting, nausea, diarrhea, anorexia, rectal bleeding, and hematemesis [ 10 , 13 ]. Our patient had an acute presentation with the classic triad of abdominal pain, distention, and absolute constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation